Analysis of the Indonesian Government's Efforts to Reduce the Unemployment Rate: A Review of the Literature Study - Wagimin, Wagimin; Anggraini, Dewi Rini; Maysarah, Putri; Sobirin, Sobirin; Erinaldi, Erinaldi; Refdi, Refdi (Journal of Economics and Social Sciences (JESS), 2025)
Unemployment remains one of the major challenges faced by Indonesia. The government has implemented various policies such as the Pre-Employment Card (Kartu Prakerja), vocational education, labor-intensive programs, and regulatory reforms through the Job Creation Law. This study aims to analyze the effectiveness of the Indonesian government’s efforts to reduce unemployment based on previous research using a qualitative descriptive approach through a literature review. The findings indicate that government policies have had a positive impact on improving skills and maintaining social stability; however, their effectiveness remains limited due to weak inter-agency coordination, skill mismatches between workers and industry needs, and a lack of sustainable employment opportunities. Therefore, stronger synergy among programs and better alignment between training and industrial demands are needed to ensure that government policies have a tangible impact on reducing national unemployment rates.